Cryptocurrencies: a survey on acceptance, governance and market dynamics - Hairudin, Aiman; Sifat, Imtiaz Mohammad; Mohamad, Azhar; Yusof, Yusniliyana (John Wiley and Sons Ltd, 2020)
This paper briefly overviews several challenging dimensions pertaining to cryptocurrencies with respect to their valuation, legitimacy, design, consensual acceptance and market-based stylized facts with a view to understanding whether this new asset class indeed has the potential to become an alternative, or a replacement, to traditional fiat currencies. Our survey indicates that public embrace of cryptocurrencies continues to lag as the masses currently show reluctance in embracing cryptocurrencies as a complement, let alone a substitute to fiat counterparts. Governments have also successfully defended their sovereignty in preserving legal tender status, structural seigniorage and exclusivity. Market-based studies hint at consistent inefficiencies across the spectrum. Furthermore, whether fundamental and mining factors determine cryptocurrencies' values remain unsettled. The most promising areas of research for crypto-financial intelligentsia would be delving into establishing trial runs for central bank-backed cryptocurrencies. In addition, we highlight that several methodological and data-based obstacles remain in assessing the link between cryptocurrencies and their traditional rivals. This avenue remains a fertile ground for potential future research.